FACTOR ANALYSIS IN THE PROCESS OF DESIGNING COMPLEX OPTICAL SYSTEMS: FACTOR ANALYSIS IN THE PROCESS OF DESIGNING COMPLEX OPTICAL SYSTEMS - Stoyanov, Stiliyan; Mardirossian, Garo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
A model of factor analysis is developed in the process of designing complex optical systems. The factor analysis is very necessary when designing photometric and spectrophotometric optical-electronic devices which consist of entrance-scanning system by space, lens with inner focusing, collimator objective which ensure the entering of a parallel shaft of rays over a dispersing diffraction grate over a wave length, chamber lens and respectively a sensor. These and similar optical systems require a higher degree of elimination of the chromatic aberration, etc. which ensures a good quality of the optical system and of the obtained results.